2020
DOI: 10.5604/01.3001.0014.2622
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness assessment of diesel locomotives operation with the use of mobile maintenance points

Abstract: Based on the example of 6Dg type diesel locomotives, the paper presents a new maintenance strategy concerning periodical checks at the P1 maintenance level. Currently, such locomotives are sent off to service points every 102 hours of operation or every 14 days for a P1 level check. Studies demonstrate that the average distance to be covered by a locomotive to arrive at a service point is in excess of 60.0 km, and the quantity of fuel consumed is more than 88 litres. It is costly and time consuming to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The typical corrective maintenance cost comes from maintenance actions resulting from inspection and review of corrective maintenance activity [39]. Szkoda, et al [40] identified that the performance of inspection activity in the rolling stock maintenance correlates with the arrival of rolling stock by shunting activity. A higher number of locomotives were used for shunting operations such as to replace the vehicle not in operation (i.e.…”
Section: Maintenance Activitymentioning
confidence: 99%
“…The typical corrective maintenance cost comes from maintenance actions resulting from inspection and review of corrective maintenance activity [39]. Szkoda, et al [40] identified that the performance of inspection activity in the rolling stock maintenance correlates with the arrival of rolling stock by shunting activity. A higher number of locomotives were used for shunting operations such as to replace the vehicle not in operation (i.e.…”
Section: Maintenance Activitymentioning
confidence: 99%
“…Energy audits related to train runs [30] and audits of traction substations [31] are also carried out. There occur investigations of the energy balance for different modes of transport moving through urban networks [32] and the overall efficiency of rail transport [24], as well as specific locomotive models [33].…”
Section: Literature Reviewmentioning
confidence: 99%